Study of human reliability in aircraft maintenance. - Espinosa, Luisa; Rebolledo, Argenis; Irausquín, Ignacio; Quiroga, Alfonso (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This research work deals with the development of a survey model designed to collect information about functional behavior of the operative personnel working for an aircraft maintenance company devoted to service general aviation (small aircraft of less than 12,500 pounds). The reliability model was based on different factors affecting the workers performance during the productive activity of the company. Influencing factors considered were: training, development, ergonomics, ownership, communication and human needs, as proposed by Abraham Maslow. The model used facilitates a better understanding of the causes that stimulate workers to do a better work to the benefit of their organization. Once the model was carefully validated and the field data was acquired at the company facilities, the values obtained with the Maslow model were analyzed by means of graphical representation. Results were used as a starting point to generate human reliability strategies in order to improve processes and maintenance operations in the aviation maintenance company under study.